War, Memory, and National Identity in the Hebrew Bible - Wright, Jacob L. (Humanities, 2020)
Drawing on the intriguing interdisciplinary research on war commemoration, the book shows that war pervades the pages of the Bible because its authors were engaged in an effort to forge a corporate identity for Israel, one that can both transcend deep divisions within the population and withstand military conquest by imperial armies.